Food insecurity is associated with decreased quality of life in patients with chronic Chagas disease - Celson Júnio do Nascimento Costa; Paula Simplício da Silva; Roberto Magalhães Saraiva; Luiz Henrique Conde Sangenis; Marcelo Teixeira de Holanda; Gilberto Marcelo Sperandio da Silva; Fernanda de Souza Nogueira Sardinha Mendes; Isis Gabrielli Gomes Xavier; Henrique Silveira Costa; Tatiana Rehder Gonçalves; Luiz Fernando Rodrigues Junior; Cristiane da Cruz Lamas; et al. (PLoS ONE, 2025)
This study assessed the prevalence of food insecurity (FI) in patients with Chagas Disease (CD) and its association with anthropometric measurements, comorbidities, and quality of life (QoL). This cross-sectional study included CD patients of both sexes. The FI was evaluated using the Brazilian FI scale. Anthropometric measurements included weight, height, and waist circumference. Comorbidities included hypertension, diabetes, dyslipidemia, and obesity. Lipids and plasma glucose were collected. QoL was assessed using the Portuguese version of WHOQOL-Bref questionnaire. Linear and logistic regression models were fitted to evaluate the association between FI status and outcomes. From the 359 included participants (55.9% women, median age 62 years), 22.5% had mild, 5.6% moderate, and 2.5% had severe FI. In the adjusted models, mild FI was significantly associated with an increased odds of obesity (OR=1.83, 95%CI = 1.03 to 3.25). Moreover, significant associations were observed between FI and all QoL domains, including physical health (low FI: β = −8.43 95%CI −12.36 to −4.49; moderate/severe FI: β = −8.02 95%CI −14.11 to −1.94), psychological (low FI β = −5.54 95%CI −9.11 to −1.96; moderate/severe FI β = −7.22 95%CI −12.76 to −1.68), social relationship (low FI: β = −6.62 95%CI −10.37 to −2.88), environment (low FI: β = −8.79 95%CI −11.99 to −5.60; moderate/severe FI β = −13.56 95%CI −18.51 to −8.62), and overall (low FI β = −8.10 95%CI −12.15 to −4.06; moderate/severe FI: β = −16.82 95%CI −23.08 to −10.57). FI was consistently associated with poor QoL in patients with chronic CD.